EXTRACTION AND PHYSICOCHEMICAL CHARACTERIZATION OF ADANSONIA DIGITATA L. MUCILAGE : Adansonia digitata mucilage (ADM) extraction and characterization (Nigerian Journal of Pharmaceutical Research, 2023)
Background: Adansonia digitata leaves are edible and they contain a significant amount of mucilage that has shown potentials for pharmaceutical application. However, there is paucity of information on this mucilage contained in its leaves.Objective: This study aimed to determine a suitable method for Adansonia digitata mucilage (ADM) extraction as well as to characterize its physicochemical properties.Materials and Methods: Physicochemical characterization was based on viscosity, chemical composition, particle size characterization via QICPIC, Scanning Electron Microscopy (SEM), Nuclear magnetic resonance (NMR), moisture content and Dynamic vapor sorption (DVS) studies as well as pH and aqueous solubility tests. In addition to this, colour of the mucilage and thermal analysis via DSC were used as criteria for selection of the most suitable method for extraction of ADM.Results: Colour and thermal analysis revealed a level of purity in the extraction process. The irregular needle like structures of ADM revealed by SEM was found to be mildly acidic with a high viscosity that is concentration dependent in aqueous medium. Thermal characterization revealed a glass transition (Tg) and melting temperatures (Tm) of 55.61 °C and 179.10 °C respectively. Finger prints of functional groups revealed azo aromatic groups and other chemical constituents of sugars including glucose, galactose, arabinose and rhamnose, and sugar acid form of galacturonic acid were identified by NMR. Moisture sorption provided insight into water sorption mechanism, processing, packaging and storage conditions of the mucilage.Conclusion: Extraction of ADM via a heat free method improved its colour and purity based on the technique used.  The mucilage was found to be a highly viscous and hydrates rapidly with good gelling properties. These properties its potential for many pharmaceutical applications including binding, coating, gelling agents as well as matrix forming. In addition its moisture sorption characteristics and glass transition temperature gave insight into its stability, storage and packaging conditions.
Keywords: Glass transition; sugar acids; viscosity; Adansonia digitata mucilage; needle-like shape